THE RAPID AND GREEN HAIR ANALYSIS METHOD DEVELOPMENT USING FTIR FOR PAPAVERINE HCL DETERMINATION - NUGRAHANI, ILMA; SULISTIANA, STEPHANIE; IBRAHIM, SLAMET (International Journal of Applied Pharmaceutics, 2019)
Objective: This study was aimed to develop a rapid analysis using FTIR (Fourier Transform Infra-Red) for papaverine hydrochloride (HCl) determination in the hair sample, supported by a mathematically manipulation; which never been reported before in toxicology and forensic analysis. Methods: Firstly, the method was checked its validity to ensure the feasibility for the quantitative purpose. The absorbance spectrums were collected by measure the drug, matrix, and its mixture. A spectra which showed the best specificity and linearity then was selected and derived. Afterwards, the area under the curve (AUC) was measured. A series of concentration was used for compose the calibration curve. Based on the result, some validation parameters were checked thoroughly. Further, for sample preparation, hair was collected non-invasively, then was decontaminated using soap. Next, it was immersed into a papaverine HCl solution at a concentration of 25 mg/ml along days. Finally, the amount of drugs absorbed were measured by the developed method using FTIR. Results: Experimental data showed that all validation parameters could be fulfilled by the developed method. The selected spectra for the content determination was 1320-1230 cm-1. Its linearity was represented by a correlation coefficient value (r) ≥ 0.9999, variation coefficient (Vxo) ≤ 2.0%. The limit of detection (LOD) was 0.00618% w/w, meanwhile, the limit of quantitation (LOQ) was 0.02060% w/w, respectively. The percent recovery was in the range 97-103% with the relative standard deviation (RSD) was ≤ 2.0%. The drug has detected after 72 h immersion, moreover, after 192 h the concentration gained was 0.1594±0.0011% w/w. Conclusion: As the conclusion, FTIR absorbance-derivative method is adequate as a rapid procedure for determine papaverine HCl in the hair sample. This method shows the appropriate of specificity, accuracy and precise. In addition, it shows the advantages of simplicity, green/eco-friendlier, and cost-efficiency.